Capital and goods market integration and the inequality of nations - Martin Wagner (Institute for Advanced Studies (IHS), 1999)
A 2-country model with two groups of agents, workers and capitalists is presented in which economic integration results in an initial phase of catch-up, where the less industrialised country experiences the rise in both capital and labour income. Then, after a certain level of integration has been reached, the less industrialised country is completely de-industrialised. This has detrimental effects on the income of this country's workers, but the capital owners of this country gain from specialisation, as do the workers in the industrialised country. Both the capital and the goods markets are subject to imperfections. The structure of the equilibrium sets during integration is characterised completely.
Keywords: F12; F15; 330; globalisation; trade; market imperfections; integration; Globalisierung; Internationale Arbeitsteilung; Marktintegration; Unvollkommener Markt; Zwei-Länder-Modell; Theorie